THE ROLE OF PHYSICAL AND PSYCHOLOGICAL APPROACHES IN PREVENTING POSTURAL DISORDERS IN ADOLESCENTS PREPARING FOR MILITARY SERVICE - D. G. Abdullaeva; D. A. Olimboeva (Web of Journals Publishing, 2025)
Postural disorders are a significant concern among adolescents, particularly those preparing for military service, where physical endurance and musculoskeletal health are crucial. This study explores the impact of combined physical and psychological approaches in preventing postural disorders in young individuals undergoing military training. The research was conducted among adolescents aged 14–16 in Uzbekistan, focusing on educational and motivational interventions aimed at improving posture. Results indicate that integrating physical training with psychological support significantly enhances postural stability, self-confidence, and overall physical readiness. The study suggests that a multidisciplinary approach is essential for ensuring proper postural development and reducing long-term musculoskeletal complications.
Keywords: Postural disorders, military training, adolescent health, physical activity, psychological resilience, posture correction, preventive strategies.